2011
DOI: 10.1002/ijc.26264
|View full text |Cite
|
Sign up to set email alerts
|

3‐Deazaneplanocin A is a promising therapeutic agent for the eradication of tumor‐initiating hepatocellular carcinoma cells

Abstract: Recent advances in stem cell biology have identified tumor-initiating cells (TICs) in a variety of cancers including hepatocellular carcinoma (HCC). Polycomb group gene products such as BMI1 and EZH2 have been characterized as general self-renewal regulators in a wide range of normal stem cells and TICs. We previously reported that Ezh2 tightly regulates the self-renewal and differentiation of murine hepatic stem/progenitor cells. However, the role of EZH2 in tumor-initiating HCC cells remains unclear. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(81 citation statements)
references
References 37 publications
6
73
1
Order By: Relevance
“…We reported previously that DZNep, but not 5-fluorouracil, reduced the number of tumor-initiating cells significantly in a mouse model of hepatocellular carcinoma. 20 Together with AML's higher requirement for EZH2, it could be a potential target for epigenetic therapy aimed at the leukemic stem cells in AML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported previously that DZNep, but not 5-fluorouracil, reduced the number of tumor-initiating cells significantly in a mouse model of hepatocellular carcinoma. 20 Together with AML's higher requirement for EZH2, it could be a potential target for epigenetic therapy aimed at the leukemic stem cells in AML.…”
Section: Discussionmentioning
confidence: 99%
“…DNZep, an S-adenosylhomocysteine hydrolase inhibitor, has been shown to eradicate tumor-initiating hepatocellular carcinoma cells and to induce apoptosis preferentially in cancer cells in other cancers, including AML. [20][21][22] DZNep inhibits S-adenosylhomocysteine hydrolase and causes the retention of S-adenosylhomocysteine, thereby inhibiting S-adenosyl-L-methionine-dependent methyltransferases such as EZH2. 23 However, DZNep is not a specific inhibitor of EZH2, so it affects other S-adenosyl-L-methionine-dependent methyltransferases For personal use only.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as a selfrenewal regulator, EZH2, modulates the self-renewal and © 1996-2015 differentiation of hepatic stem cells. 3-Deazaneplanocin A (DZNep), an EZH2 pharmacological inhibitor, decreased EpCAM + T-IC subpopulation and suppressed tumorigenesis in NOD-SCID mice (117). In this context, the use of EZH2 inhibitors, such as an S-adenosylhomocysteine hydrolase inhibitor, DZNep, might be a promising strategy through targeting hepatic T-ICs (117).…”
Section: Discussionmentioning
confidence: 99%
“…3-Deazaneplanocin A (DZNep), an EZH2 pharmacological inhibitor, decreased EpCAM + T-IC subpopulation and suppressed tumorigenesis in NOD-SCID mice (117). In this context, the use of EZH2 inhibitors, such as an S-adenosylhomocysteine hydrolase inhibitor, DZNep, might be a promising strategy through targeting hepatic T-ICs (117). A demethylating agent, zebularine, increased self-renewal and tumorigenicity of low density HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Report revealed that the use of agent disrupting PRC2 subunits is a relevant way to affect PRC2 function (Tan et al, 2007). Although currently there is no EZH2 specific inhibitor, but agent such as DZnep is also able to deplete the cellular EZH2, inhibit EZH2 functions and lower the H3K27 trimethylation level (Chiba et al, 2011). This fundamental knowledge surely enables researchers to design potent agents to target EZH2 in HCC.…”
Section: Ezh2mentioning
confidence: 99%